Haiti : the tumultuous history : from pearl of the Caribbean to broken nation - Girard, Philippe (Palgrave Macmillan, 2010)
"In the aftermath of January's horrific earthquake, the world's attention is focused on Haiti. In this full narrative history of the Caribbean nation, historian Philippe Girard offers insight into Haiti's complex and layered past, showing that its current state as the poorest country in the western hemisphere was not inevitable. This highly readable and accessible history takes the reader back two hundred years to a time when Haiti was so prosperous it was known as the Pearl of the Antilles. Haiti was the only country in the Americas to pull off a successful slave revolution, yet today its survival is completely dependent on foreign aid. As all eyes turn to watch what happens to Haiti, author Girard provides the necessary context for envisioning its future--including a detailed account of the quake's consequences, an assessment of the benefit and cost of an American intervention, and commentary on what Haiti must do to rebuild for a brighter future"--
Keywords: historia; poliittinen historia; politisk historia; Haiti : History; Haiti